1999
DOI: 10.1213/00000539-199912000-00038
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Visual Analog Scale: Is It Linear or Nonlinear?

Abstract: To the Editor:-I have spent some time considering the conclusions reached by Aubrun et al. 1 in their study investigating the relationship between the pain visual analogue scale (VAS) and morphine requirements in the postanesthesia care unit. They demonstrated that the Hill equation could be used to derive a sigmoid relationship between the pain VAS and morphine dosage, and concluded that this relationship is not linear. In their discussion, they referred to an earlier study in which I and colleagues had found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(94 citation statements)
references
References 20 publications
1
80
1
5
Order By: Relevance
“…The second assumption is that they incorporate the same level of measurement. There is debate in the literature on this point—that is, whether the VAS and VNRS are ratio, interval or ordinal scales in all circumstances 26 27 29 30. In keeping with a range of other studies, we have adopted the simpler approach of treating both scales as being measured at the same level 19 20 24 25.…”
Section: Limitationsmentioning
confidence: 99%
“…The second assumption is that they incorporate the same level of measurement. There is debate in the literature on this point—that is, whether the VAS and VNRS are ratio, interval or ordinal scales in all circumstances 26 27 29 30. In keeping with a range of other studies, we have adopted the simpler approach of treating both scales as being measured at the same level 19 20 24 25.…”
Section: Limitationsmentioning
confidence: 99%
“…18 Thus, the tPM parameters (especially the E max ) could have displayed a better linearity than VAS, but this was not confirmed here, although a better reliability to the intensity of stimulation with the tPM parameters was suggested by the lower Bmismatching rate[ at the 2 higher levels of stimulation, with the 2 tPM parameters. It must be added that, as for ethical reasons, the maximal intensity of stimulation was limited, very high pain intensities (ie, pain scores on VAS 980/100) were not frequently reached; then, the loss of linearity of the VAS scores, which has been reported at levels of intense pain, 6 could have been masked in the present experiment.…”
Section: Discussionmentioning
confidence: 96%
“…Painful stimulation was generated with an infrared CO 2 laser stimulator, a system able to generate predictable levels of punctuate pain, after the amount of energy delivered. 12 We worked under the hypothesis that the reported pain intensity would display a linear relation to the intensity of stimulation in the conditions of the study because (i) such linearity is suggested for VAS in the range of moderate pain (30Y50/100) 6 and (ii) the cross-modality matching of force of handgrip to warmth on the arm following a Stevens power function exponent is close to 1 (0.96). 13 …”
mentioning
confidence: 99%
“…Good pain control was defined as a score of ≤3 on the Faces, Legs, Activity, Cry, Consolability tool (FLACC),18 Visual Analog Scale (VAS),19 or Neonatal Infant Pain Scale (NIPS),20 or a score of ≤5 on the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS) 21. Additionally, patients had to reach an appropriate level of sedation (or wakefulness) before they could be transferred to the floor.…”
Section: Methodsmentioning
confidence: 99%